REAKSI PASAR MODAL INDONESIA TERHADAP PERISTIWA BENCANA ALAM TSUNAMI DI ACEH TANGGAL 26 DESEMBER 2004 - Nungky Viana Feranita (Majalah Ilmiah DIAN ILMU, 2014)
As one of an instrument of economy, capital market can not be separated from influence that amend in its environment, either occur in macro economic, micro economic or non-economic environment. This research is one of the event study which examined in how the reaction of Indonesian capital market toward event that occur in an non-economic environment which is tsunami natural disaster in Aceh, December 26th, 2004.The purpose of this research is to examine stock prices reaction and trading volume activities in Jakarta Stock Exchange (JSX) toward tsunami natural disaster event in Aceh, also to examine whether there are any differences in average abnormal return and average trading volume activity before and after tsunami natural disaster event in Aceh. The samples are generated from stocks that have the biggest market capitalization in JSX which are often listed in LQ45 in period August, 2003 until January, 2008.The result of test using SPSS with 95% confidence level shows that JSX was not responded toward tsunami natural disaster event in Aceh. This is shown by no abnormal return during event period, no difference of average abnormal return before and after event, and no difference of average trading volume activity before and after tsunami natural disaster event in Aceh.